Impaired transmissibility of atypical prions from genetic CJD(G114V) - Cali, Ignazio (Neurol Genet, 2018)
OBJECTIVE: To describe the clinicopathologic, molecular, and transmissible characteristics of genetic prion disease in a young man carrying the PRNP-G114V variant. METHODS: We performed genetic, histologic, and molecular studies, combined with in vivo transmission studies and in vitro replication studies, to characterize this genetic prion disease. RESULTS: A 24-year-old American man of Polish descent developed progressive dementia, aphasia, and ataxia, leading to his death 5 years later. Histologic features included widespread spongiform degeneration, gliosis, and infrequent PrP plaque-like deposits within the cerebellum and putamen, best classifying this as a Creutzfeldt-Jakob disease (CJD) subtype. Molecular typing of proteinase K-resistant PrP (resPrP(Sc)) revealed a mixture of type 1 (∼21 kDa) and type 2 (∼19 kDa) conformations with only 2, rather than the usual 3, PrP(Sc) glycoforms. Brain homogenates from the proband failed to transmit prion disease to transgenic Tg(HuPrP) mice that overexpress human PrP and are typically susceptible to sporadic and genetic forms of CJD. When subjected to protein misfolding cyclic amplification, the PrP(Sc) type 2 (∼19 kDa) was selectively amplified. CONCLUSIONS: The features of genetic CJD(G114V) suggest that residue 114 within the highly conserved palindromic region (113-AGAAAAGA-120) plays an important role in prion conformation and propagation.